Rain anomaly index applied to the study of rainfall in the CRAJUBAR region - Ceará - Bezerra de Melo, Rayanne (2024)
Extreme precipitation events, such as droughts or heavy rains, cause several damages to society and one way to monitor the occurrence of these events is through the Rainfall Anomaly Index (CAI). The CRAJUBAR region of Ceará, composed of the municipalities of Crato, Juazeiro do Norte and Barbalha, as well as other municipalities in northeastern Brazil, is marked by years of severe droughts or heavy rains concentrated in a short period, influenced, among other phenomena, by the occurrence of El Niño Southern Oscillation in its hot (El Niño) and cold (La Niña) phases. Thus, this work had as its main objective to characterize and analyze the rainfall regime of the Cariri region, through the application of the IAC for the years that make up the historical series from 1974 to 2021, checking its relationship with the ENSO. The rainfall records were made available by the Meteorology and Water Resources Foundation of Ceará (FUNCEME) and from these, without the need for filling in gaps, the IAC was calculated for each year studied in each municipality, and the results are illustrated together with the occurrence of ENSO in a graph. Of the extreme occurrences both positive and negative of precipitation, less than half were concomitant to ENSO, including in the municipality of Barbalha, in 1976, there was moderate drought despite the occurrence of La Niña in moderate intensity. From another perspective, of the years with ENSO influence, few of them had moderate to intense anomalies of flood or drought.